Analisis Struktur dan Makna Pada Mantra Jangjawokan Di Kecamatan Malingping Sebagai Bahan ajar Apresiasi Sastra Indonesia Di SMA - Suhemi, Cepi (Universitas Mathla'ul Anwar Banten, 2023)
This study aims to obtain a description of the structure of the mantra text, the structure and meaning of the mantra in society as well as the inheritance of the mantra in general that has developed in the community of the Galunggung-Malingping mountain area. This study focuses on oral traditions that contain local wisdom. Mantra is one form of oral tradition that lives and develops in a society. The method used is descriptive qualitative. The analysis was carried out with an objective approach. The objective approach views that literary works consist of several elements that build each other. Analysis based on an objective approach in the mantra of affection, namely containing sound conformity, both vowel and consonant sounds, syntactic unity, bound by the context of narration, function, and the process of inheritance from generation to generation.